Ação de protease do látex de Ficus benjamina L. sobre nematôdeo e bactérias de interesse na produção animal - WANDERLEY, Lêdia Feitosa (2016)
Helminthes and bacterial infections are a major challenge for livestock production because they cause loss of productivity in herds. To reduce losses, producers control parasites and bacteria mainly using synthetic chemicals, but the resistance to the active principles of these products calls for the continuous search for biologically active molecules. This research was conducted with the objective of obtaining protein fractions and protease from the latex of Ficus benjamina, in addition to evaluating the potential use of these protein samples in the control of the parasite nematode of small ruminants, Haemonchus contortus, as well as on the pathogenic bacteria Salmonella enterica, Staphylococcus aureus and Enterobacter aerogenes. Latex was obtained from an incision made at the apex of the plant limb and collected in sodium phosphate buffer (75 mM, pH 7.0). The latex was centrifuged (12,000 x g at 4 ° C for 15 min), dialysed against water (14 kDa cut-off), again centrifuged under the same conditions as before and then referred to as EPL (Latex Protein Extract). The EPL was fractionated with ammonium sulphate at 30-60% and 60-90% saturation to obtain the fractions denominated F30-60 and F60-90, respectively. F60-90 was fractionated by ion exchange chromatography on CM-Cellulose matrix and the fraction with the highest proteolytic activity obtained was denominated FbP (Ficus benjamina Protease). With these fractions, protein analysis, proteolytic activity and FbP identification were carried out. In addition, inhibition of larval development of the nematode H. contortus and inhibition of the growth of S. enterica, S. aureus and E. aerogenes in a liquid medium were carried out. The total protein levels obtained were, respectively, 121.5, 21.2, 75.7 mg for EPL, F30-60 and F60-90. The proteolytic activity of the protein samples was 43,471, 13,245 and 57,857 UA/mL/mgP for EPL, F30-60 and F60-90, respectively. The FbP presented proteolytic activity of 36,393.8 AU/mL/mgP. Gel analysis showed FbP with a protein band with mass between 20 and 30 kDa and by mass spectrometry the FbP was identified as cysteine protease, with a molecular weight of 23.97 kDa. FbP maintained stable proteolytic activity in the pH range between 6 and 10 and over a wide temperature range, with optimum activity at 60 °C. In tests for inhibition of larval development, EPL, F30-60, F60-90 and FbP presented IC50 of 0.22, 1.38, 0.42 and 0.26 mg/mL, respectively. It was verified that EPL, F30-60 and F60-90 did not exert an inhibitory action on the growth of bacteria, but FbP inhibited the growth of S. aureus and S. enterica with minimum inhibitory concentration (MIC) of 3.12 μg/mL. It is concluded that FbP obtained from latex of F. benjamina has promising biological properties for the development of products that can be used in the control of the gastrointestinal nematode, H. contortus, and the pathogenic bacteria S. aureus and S. enterica.